2008
DOI: 10.1124/jpet.107.134619
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial Dysfunction in Rat Mesenteric Resistance Artery after Transient Middle Cerebral Artery Occlusion

Abstract: Stroke triggers a local and systemic inflammatory response leading to the production of cytokines that can influence blood vessel reactivity. In this study, we aimed to assess whether cerebral ischemia/reperfusion could affect vasoconstriction and vasodilatation on mesenteric resistance arteries (MRA) from Wistar Kyoto rats. The right middle cerebral artery was occluded (90 min) and reperfused (24 h). Sham-operated animals were used as controls. Plasma levels of interleukin (IL)-6 and IL-1␤ were measured at 24… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 39 publications
1
32
0
Order By: Relevance
“…Frozen transverse sections (14 m) of MCA were processed as described previously (Martinez-Revelles et al, 2008). Sections were incubated with a rabbit primary polyclonal antibody against nitrotyrosine (1:150; Millipore, Billerica, MA).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Frozen transverse sections (14 m) of MCA were processed as described previously (Martinez-Revelles et al, 2008). Sections were incubated with a rabbit primary polyclonal antibody against nitrotyrosine (1:150; Millipore, Billerica, MA).…”
Section: Methodsmentioning
confidence: 99%
“…Peroxynitrite is produced from the interaction of NO and O 2 . and present during focal cerebral ischemia not only in brain tissue (Warner et al, 2004;Romanos et al, 2007) but also in blood vessels (Maneen et al, 2006;Martinez-Revelles et al, 2008). Increasing evidence indicates that ONOO Ϫ can have deleterious effects on cerebral blood vessels (Faraci, 2006;Iadecola and Davisson, 2008).…”
Section: Oxidative Stress and Remodeling After Ischemiamentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that the endothelium-dependent relaxation was reduced in isolated arteries from different animal models of hypertension [40] as well as in hypertensive patients [41, 42]. In addition, ischemic stroke impaired the endothelium in cerebral arteries [43] and mesenteric arteries [44] from normotensive rats and stroke patients [45]. None of these results can be related to our results, since we observed an increased carbachol-induced dilating response in the ischemic cerebral arteries from hypertensive rats.…”
Section: Discussionmentioning
confidence: 99%
“…Teixeira and coworkers have demonstrated that, in the model of superior mesenteric artery I/R injury in rats, remote lung injury occurs, evidenced by increased vascular permeability and neutrophil accumulation (Souza et al 2001). Martinez-Revelles et al (2008) have shown that transient middle cerebral artery occlusion can induce endothelial dysfunction in rat mesenteric resistance artery. However, the effects of myocardial I/R on peripheral arteries remain unclear.…”
mentioning
confidence: 99%